Increasing Self Regulated Learning of Students with Special Needs Through the ILBaWEL Model - Marlina . (Department of Special Education, 2017)
This study aims to increase self regulated learning of students with special needs in the course of Educational Psychology through the application of Model Inquiry Learning Berbasis Web Enhanced Learning (ILBaWEL). The study used single subject design with multiple baseline cross subject. Data were collected through observation, interviews, and test. Subjects consisted of five students with special needs, which consists of one person with a hearing impairment and four persons with visual impairment who took a course of Educational Psychology at the State University of Padang. Five (5) students with special needs to apply the ILBaWEL Model in the course of Educational Psychology. The results of the research showed that (1) the ILBaWEL Model have the accuracy, appropriateness and usefulness to be applied in the course of Educational Psychology because it emphasizes student activities to seek and find, develop the ability to think systematically and logically and critically, facilitate learning interaction from anywhere and anytime, has a wider range, easy to use by faculty and students, and is a learning model prescriptive components consist of a set of systematic learning steps; (2) the application of ILBaWEL Model in the lecture consists of six stages, namely orientation, define problems, propose a hypothesis, collect data, test hypotheses, and conclusions; (3) the ILBaWEL Model was effective for increasing the self regulated learning of students with special needs in the course of Educational Psychology. There is an increased score of self regulated learning significantly from the baseline phase to the intervention phase.